PERCEPCIÓN DE LOS PARTIDOS POLÍTICOS EN EL ÁREA ANDINA Y SUS EFECTOS SOBRE LA DEMOCRACIA - Mansilla, H.C.F. (Universidad de Costa Rica, 2023)
This essay is an analysis of the main political and cultural problems connected with the accelerated modernization in the Andean area since 1980. Ecuador, Peru and Bolivia experience now a growing disillusion with the political parties and also with the democratic system (antipolitics), which may have incalculable consequences, for the traditional political culture of authoritarianism is still very strong.